Alberto Guerreiro Ramos, 20 years later: a new science still unrealized in an era of public cynicism and theoretical ambivalence - Ventriss, Curtis; Candler, Gaylord George (2005)
Alberto Guerreiro Ramos's public life and scholarly works challenge us to rethink and reconceptualize the field of public administration, particularly in this area of public cynicism and theoretical uncertainty. This article examines the historical context of his earlier writings and how they influenced his later scholarly work. As a prominent Brazilian scholar working in the United States, Guerreiro Ramos's "in-betweeness" as he called it, provided him a unique and little-appreciated perspective from which to reevaluate the social sciences. The result was his last book, The New Science of organizations: A Reconceptualization of the wealth of nations, one of the most polemical works published in the field and an examination of the fundamental assumptions of public administration and the social sciences. - Reproduced.
Keywords: Public administration